Mental health inequalities in disruptions across multiple domains during COVID -19: an investigation in 12 population-based longitudinal studies. (20th October 2021) - McElroy, E; Di Gessa, G; Maddock, J; Green, MJ; Thompson, EJ; Davies, HL; Mundy, J; Stevenson, AJ; Kwong, ASF; Patalay, P
Abstract: Disruptions related to the COVID-19 pandemic and its associated virus suppression measures have affected many worldwide but those already suffering from psychological distress may have been especially vulnerable. We investigated associations between pre-pandemic psychological distress and disruptions to healthcare, economic activity, housing, and cumulative disruptions. Data were from 59, 482 participants in 12 UK longitudinal adult population surveys with both pre-pandemic and COVID-19 surveys. Participants self-reported disruptions since the start of the pandemic to: healthcare (medication access, procedures, or appointments); economic activity (negative changes in employment, income or working hours); and housing (change of address or household composition). Logistic regression models were used to estimate associations between pre-pandemic standardised psychological distress scores and disruption outcomes. Findings were synthesised using a random effects meta-analysis with restricted maximum likelihood. Approximately one to two thirds of study participants experienced some form of disruption during the pandemic. One standard deviation higher pre-pandemic psychological distress was associated with: increased odds of any healthcare disruption (odds ratio: 1.30 [95% CI: 1.20-1.40]; I2: 65%); increased odds of experiencing any economic disruption (1.11 [1.03-1.16]; I2: 61%); no associations with housing disruptions; and increased likelihood of experiencing a disruption in at least two domains (1.25 [1.18-1.32]; I2: 38%) or one domain (1.11 [1.07-1.16]; I2: 32%) compared to no disruptions. Associations did not differ by sex, ethnicity, education, or age. Individuals suffering from psychological distress pre-pandemic may need additional support to manage stressful life disruptions. Considering mental ill-health was already unequally distributed in the UK population, this may exacerbate existing inequalities related to sex, ethnicity, education and age.